2023
DOI: 10.1111/febs.16720
|View full text |Cite
|
Sign up to set email alerts
|

Multiple enzymatic approaches to hydrolysis of fungal β‐glucans by the soil bacterium Chitinophaga pinensis

Abstract: The genome of the soil Bacteroidota Chitinophaga pinensis encodes a large number of glycoside hydrolases (GHs) with noteworthy features and potentially novel functions. Several are predicted to be active on polysaccharide components of fungal and oomycete cell walls, such as chitin, β‐1,3‐glucan and β‐1,6‐glucan. While several fungal β‐1,6‐glucanase enzymes are known, relatively few bacterial examples have been characterised to date. We have previously demonstrated that C. pinensis shows strong growth using β‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Previously characterised examples of CBM92-containing proteins bound to β−1,3-glucan 11 and carrageenan 6 : both of those domains bind to the same polysaccharide as their appended enzymes can target, suggesting a likely role in enzyme potentiation 2 . Indeed, our phylogenetic analyses show that a number of CBM92 domains are attached to predicted β−1,6-glucanases from enzyme family GH30 (sub-family 3) 55 , and these may be expected to show the same kind of rate potentiation. The natural substrate for these enzymes may be polymeric pustulan as found in lichenous fungi 20 or it may be shorter chains of β-1,6-glucan such as can be found in the cell walls of certain oomycetes 18 .…”
Section: Resultsmentioning
confidence: 89%
“…Previously characterised examples of CBM92-containing proteins bound to β−1,3-glucan 11 and carrageenan 6 : both of those domains bind to the same polysaccharide as their appended enzymes can target, suggesting a likely role in enzyme potentiation 2 . Indeed, our phylogenetic analyses show that a number of CBM92 domains are attached to predicted β−1,6-glucanases from enzyme family GH30 (sub-family 3) 55 , and these may be expected to show the same kind of rate potentiation. The natural substrate for these enzymes may be polymeric pustulan as found in lichenous fungi 20 or it may be shorter chains of β-1,6-glucan such as can be found in the cell walls of certain oomycetes 18 .…”
Section: Resultsmentioning
confidence: 89%
“…According to the CAZymes classification, [16] the closest homologues of PsGly30A belong to the GH30_3 subfamily. The closest homologue of PsGly30A for which a crystal structure (PDB ID: 5NGK) has been determined is endo‐β‐1,6‐glucanase BT3312 from Bacteroides thetaiotaomicron , [14] with a sequence similarity of 32 % and the closest characterised member of the GH30 family is Cp Glu30 A from Chitinophaga pinensis , [13] which belongs to the GH30_3 subfamily, with sequence identity of 40 %.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the compounds obtained after hydrolysis of a hydrothermally treated pustulan with PsGly30A showed that gentiobiose was the main product (Figure 6b). In comparison, glucose was the major product produced from pustulan after prolonged hydrolysis using BT3312 from Bacteroides thetaiotaomicron, [14] CpGlu30A from Chitinophaga pinensis, [13] GH30A from Coprinopsis cinerea, [31] and Gly30B from Saccharophagus degradans. [27] As expected, hydrolysis of yeast β-glucan and yeast CW using PsGly30A resulted in significantly lower concentrations of gentiobiose and a similar pattern of additional products besides gentiobiose, compared to pustulan hydrolysis.…”
Section: Production Of Gentiobiose By Means Of Enzymatic Hydrolysis O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, to enhance oligoglucoside hydrolysis, a thermostable β-1,3-glucanase from Trichoderma harzianum was expressed in Pichia pastoris [11,17]. Meanwhile, β-1,3-glucanases from Chitinophaga pinensis hydrolyze β-1,6-glucan pustulan and can be classified into different GH families with different levels of β-1,6-glucanase activity [18]. In the control of fungal pathogens, some biocontrol agents showed interest in beta-1,3-glucanase production.…”
Section: Introductionmentioning
confidence: 99%